Evaluation of the Cost-Utility of the York Faecal Calprotectin Care Pathway. (3rd April 2022) - Holmes, Hayden; McMaster, Jessica; Davies, Heather; Vaines, Victoria; Turvill, James
ABSTRACT: Background : Lower gastrointestinal symptoms are common in the general population and it can be difficult to discriminate between inflammatory bowel disease (IBS) and irritable bowel syndrome (IBD) due to overlap of symptoms. The York Fecal Calprotectin Care Pathway (YFCCP) was introduced in 2016 as an alternative to the NICE fecal calprotectin pathway (DG11). This analysis uses the prospective data from the first 1005 patients in the YFCCP. Previous analysis demonstrated the YFCCP may be cost-saving when compared with the DG11 pathway. This analysis examined the short-term health-related quality of life (HRQoL) impact for patients in the YFCCP for IBD and IBS. Methods : A decision tree model was used to estimate the proportion of people presenting with lower gastrointestinal symptoms that were correctly or falsely diagnosed with IBS and IBD. Time to diagnosis data was estimated and HRQoL data was estimated from published sources. Costs and QALYs were calculated for the YFCCP and each comparator. Results : The YFCCP was cost-effective at a £20, 000 threshold when compared with the current NICE recommended pathways and was cost-saving with a QALY gain (dominant)in four of the five comparators. Conclusions: The YFCCP demonstrated a QALY benefit when compared with all alternative pathways.